Effect of surgical intervention on circulating tumor cells in patients with squamous cell carcinoma of the head and neck using a negative enrichment technology. Issue 12 (5th June 2016) - Jatana, Kris R.; Balasubramanian, Priya; McMullen, Kyle P.; Lang, Jas C.; Teknos, Theodoros N.; Chalmers, Jeffrey J.
ABSTRACT: Background: The purpose of this study was to investigate the impact of surgical intervention on detection of circulating tumor cells (CTCs) in patients with squamous cell carcinoma of the head and neck (SCCHN.) Methods: We utilized a negative depletion technique to identify cytokeratin (CK)‐positive CTCs. The numbers of CTCs immediately before and after surgical resection were compared. Results: Seventy‐six blood samples from 38 patients with SCCHN were examined. Seventy‐nine percent of the patients had CTCs detected before and after surgery. A total of 7.89% had no CTCs before surgery, yet had CTCs identified after surgery. Overall, 60.5% of patients had an increased number of CTCs/mL after surgery with a mean increase of 6.63‐fold. A statistically significant increase in CTCs was seen after surgery ( p = .02). Conclusion: The timing of sample collection in patients with SCCHN who have surgical intervention can potentially impact the number of CTCs identified. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1799–1803, 2016